2010
DOI: 10.1016/j.neuroimage.2010.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Identifying robust and sensitive frequency bands for interrogating neural oscillations

Abstract: Recent years have seen an explosion of interest in using neural oscillations to characterize the mechanisms supporting cognition and emotion. Oftentimes, oscillatory activity is indexed by mean power density in predefined frequency bands. Some investigators use broad bands originally defined by prominent surface features of the spectrum. Others rely on narrower bands originally defined by spectral factor analysis (SFA). Presently, the robustness and sensitivity of these competing band definitions remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 165 publications
2
70
0
1
Order By: Relevance
“…These frequency bands were defined on the basis of factorial analysis of EEG records [55,56,57] and thereby constitute a very robust framework. It does not mean that other frequency ranges shall not be used for specific purposes [58]. However, to ensure that the results of a study can be compared with others published and therefore can provide useful reference material for other scientists, publications should always report the results obtained for this standard configuration (beside others if appropriate).…”
Section: Pharmaco-eeg – Data Processingmentioning
confidence: 99%
“…These frequency bands were defined on the basis of factorial analysis of EEG records [55,56,57] and thereby constitute a very robust framework. It does not mean that other frequency ranges shall not be used for specific purposes [58]. However, to ensure that the results of a study can be compared with others published and therefore can provide useful reference material for other scientists, publications should always report the results obtained for this standard configuration (beside others if appropriate).…”
Section: Pharmaco-eeg – Data Processingmentioning
confidence: 99%
“…With the advent of robust time-frequency decompositions, investigating the evolution of brain activity in the frequency domain is possible [26,40]. Evidence suggesting that the spectral dynamics of brain activity is mounting [2,37]. Blanco et al introduced pioneering new methods for time-frequency analysis for EEG data [5].…”
Section: Related Workmentioning
confidence: 99%
“…In the article YuvalGreenberg et al (2008) suggest that the commonly reported high frequency, transient, scalp-recorded iGBR that peaks around 200-300 ms and covers a broad frequency range (e.g., Busch et al, 2006;Gruber et al, 2002;Tallon-Baudry et al, 1996;Zion-Golumbic and Bentin, 2007) is produced by electromyographic activity relating to microsaccades, rather than the coherent activity of neural sources. Naturally, this suggestion has triggered an ongoing debate as to exactly how much of the iGBR reported in previous studies can be attributed to these electromyogenic artefacts (Dimigen et al, 2009;Fries et al, 2008;Gruber et al, 2008b;Keren et al, 2010;Melloni et al, 2009b;Shackman et al, 2010;Tallon-Baudry, 2008).…”
Section: Introductionmentioning
confidence: 99%